Exploring the toxicity of styrene bio-production & the tolerance of other related organic solvents in E. coli by expressing different efflux pump systems - Muheisen, Hana'a (2019)
The toxicity of styrene is the most important obstacle facing its production biologically in E. coli using the tools of synthetic biology. One potential solution to counter this toxicity involves manipulating a membrane transporter in E. coli to export the chemical outside the cell membrane. In this project, SrpABC and AcrABTolC were used as candidate solvent pumps to investigate styrene resistance in E. coli. The solvent resistant pump, SrpABC, is a membrane protein that transports several organic solvents such as styrene and toluene out of the cell in Pseudomonas putida S12. Another important efflux system originally found in E. coli is the AcrABTolC system which expels a wide range of substrates from antibiotics to chemical solvents. SrpABC genes were expressed in E. coli MG1655 (DE3), which was modified as part of this project by the incorporation of the λDE3 lysogen into a parental E. coli MG1655. Confirmation has been obtained regarding the overexpression of recombinant SrpABC in that strain by conducting RT–PCR analysis and an improvement of the detection of SrpA protein expression by western blotting has also been done. Subsequently, the other efflux system, AcrABTolC, has been overexpressed in E. coli BW25113 and confirmed by SDS PAGE and western blot techniques. Tests of tolerance towards styrene and other organic solvents were conducted in the exponential phase of liquid cultures. The results showed that overexpressed SrpABC in E. coli confers more tolerance towards styrene than the AcrAB pump in E. coli C43 (DE3) ΔacrAB. Besides, the cells were tolerant towards cyclohexane, cyclohexene, 1, 3-cyclohexadiene and ethylcyclohexane at concentrations 25, 10, 10 and 100 mM, respectively. The effect of the SrpABC was tested on the bio-production of styrene proceeded in the same strain. Genes encoding PAL2 and FDC1 were cloned into pACYCDuet-1 and pETDuet-1 plasmids which were compatible with the efflux pump systems. The strain bearing the SrpABC pump (E. coli MG1655 (DE3)-pETDuet_pal-fdc_pACYCDuet_SrpABC) produced 8.05 mM styrene using glucose (12 g /L) and L-phenylalanine (2 g / L) in a bioreactor, 30 % higher than the strain without the pump (E. coli MG1655 (DE3)-pETDuet_pal-fdc); 6.2 mM. It was concluded that the SrpABC pump could improve styrene production.